Structural Changes in Management of Traditional Economy of North of Yakutia in 1992-1993 - Y. M. Sannikova (Научный диалог)
The article considers the fate of the traditional economy of indigenous population of the North of Yakutia in the first years of the post-Soviet decade through the prism of changes in the management structure of the agricultural sector of the region - in the part that was associated with the daily life of the farms of the Arctic and Northern territories of Yakutia and largely determined the implementation of the agricultural policy of the Republic. It is indicated that the traditional economy of the North of Yakutia is characterized by the complexity of traditional economic activities, while the leading direction is reindeer husbandry, in particular the breeding of domestic deer. Despite all the difficulties and contradictions typical for the development of Northern farms, Yakutia remained one of the largest reindeer herding regions of the country. The authors consider the structural changes in the management of Northern farms in the first post-Soviet years: search for ways to manage farms, project initiatives of the management of agricultural complex “North” and features of the formation of a unite management space in the agricultural sector of the Republic. The issue of the organization of the National joint stock reindeer herding company “Taba” is covered in more detail. On the basis of archival documents, an attempt is made to show the sequence and logic of these structural changes in the management of the traditional economy of the North of Yakutia in the early 1990s.